A simplified technique of mandibular complete denture fabrication for a condition of ankyloglossia – A case report - Pamila Mary Sabatini Melkiyor; Nagappan Chockalingam; R. Kamala Kannan (SRM Journal of Research in Dental Sciences)
Rationale: During the construction of a complete denture, obtaining adequate retention is always a problem in the mandibular denture. In the case of ankyloglossia, the retention of mandibular denture is severely compromised due to a decrease in neutral zone space and thick musculature of the tongue web attached to the mouth’s anatomical floor. Diagnosis: The patient was diagnosed as completely edentulous with ankyloglossia. Intervention: The intervention that was done to this condition was a modification of the master cast before the final wax-up and processing of the denture. Outcomes: Through the modification that was done to the master cast, an acceptable level of retention was attained. Lessons: This case report describes a simple modification that is done to achieve optimal retention for a patient with ankyloglossia and to maintain that retention during function.